2021
DOI: 10.3390/ijms22084164
|View full text |Cite
|
Sign up to set email alerts
|

A Walk in the Memory, from the First Functional Approach up to Its Regulatory Role of Mitochondrial Bioenergetic Flow in Health and Disease: Focus on the Adenine Nucleotide Translocator

Abstract: The mitochondrial adenine nucleotide translocator (ANT) plays the fundamental role of gatekeeper of cellular energy flow, carrying out the reversible exchange of ADP for ATP across the inner mitochondrial membrane. ADP enters the mitochondria where, through the oxidative phosphorylation process, it is the substrate of Fo-F1 ATP synthase, producing ATP that is dispatched from the mitochondrion to the cytoplasm of the host cell, where it can be used as energy currency for the metabolic needs of the cell that req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 177 publications
(95 reference statements)
0
11
0
Order By: Relevance
“…Recently we found that the Raman signal intensity of the band at 2845 cm -1 in lipid droplets is significantly higher for high-grade cancer of glioblastoma (U87 MG) than for normal astrocytes (NHA), indicating a higher concentration of TAGs in cancer lipid droplets [20]. The higher concentration of TAG was related to the increased amount of cytoplasmic lipid droplets in human glioblastoma cells in comparison to normal astrocytes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently we found that the Raman signal intensity of the band at 2845 cm -1 in lipid droplets is significantly higher for high-grade cancer of glioblastoma (U87 MG) than for normal astrocytes (NHA), indicating a higher concentration of TAGs in cancer lipid droplets [20]. The higher concentration of TAG was related to the increased amount of cytoplasmic lipid droplets in human glioblastoma cells in comparison to normal astrocytes.…”
Section: Resultsmentioning
confidence: 99%
“…The intensity of the band at 1654 cm -1 decreases for glioblastoma U87 MG upon incubation with mRNA. It has been reported that changes in mitochondrial membrane potential favour functional deterioration of the adenine nucleotide translocator (ANT), which belongs to mitochondrial carrier family [20]. As ANT represents about 10 % of proteins in mitochondria the observed in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The vital role of ANT is the enzymatic one, which is the historical and the main function to catalyze the carrier-mediated exchange between the cytosolic ADP with the ATP formed in the matrix, by facilitating the export of the newly synthesized ATP into the cell and, at the same time, by providing ADP as a substrate available for its mitochondrial phosphorylation to ATP by ATP synthase. This function has been extensively characterized in mitochondria isolated from various tissues with radiolabelled nucleotides and in native ANT-containing proteoliposomes [ 67 , 68 , 69 ], but not only [ 70 ], as we will see! The lethal function of ANT, which occurs in conditions of cellular ‘sickness’, is associated with its involvement as a component of the mitochondrial permeability transition pore (mPTP), a structure that forms in the inner mitochondrial membrane and is thought to underlie regulated cell death [ 71 , 72 ].…”
Section: Ant and Vdac Both Interact With Ad Toxic Proteinsmentioning
confidence: 99%
“…To perform this, having established that each peptide individually altered the activity of ANT-1, we investigated whether and how the decrease in ADP/ATP exchange induced by each peptide could vary under two different conditions: (1) when the addition of one preceded that of the other and (2) when peptides were added together with the system. The experimental procedure adopted is always the same—to which we have even dedicated a paper [ 70 ], to which the reader is referred—the one that allows the continuous monitoring of ATP efflux from neuronal mitochondria incubated with ADP [ 70 ]. Several observations were made: The rate of appearance of ATP was reduced when Aβ1–42 or NH 2- 26–44-tau was added before ADP.…”
Section: Ant and Vdac Both Interact With Ad Toxic Proteinsmentioning
confidence: 99%